Faktor–faktor yang Melatarbelakangi Kunjungan ANC pada Ibu Hamil - Erfiani Mail; Farida Yuliani; Fitria Edni Wari (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Antenatal care (antenatal care) is very important to be known by pregnant women because it can help reduce maternal and infant mortality. The preliminary study on BPS dilaksaakan Ny. “F”, Gayaman Village Subdistrict Mojoanyar Mojokerto 8 pregnant women (80%) did not perform as scheduled prenatal visit ANC and 2 pregnant women (20%) ANC visit schedule regularity ANC. The purpose of the study to determine the factors underlying the ANC in pregnant women. Type a descriptive study. Variable factors behind research ANC. Population of 35 respondents. Sampling technique that uses sampling and a total sample of 35 respondents. The experiment was conducted in BPS NY “F” on 28 January to 04 February 2021, using a questionnaire. Data collection techniques using the editing, coding, scoring, data entry, cleaning and presentation of data. Based on the results, the majority of respondents multigravida total of 19 respondents (54.3%), less than half of the respondents have socioeconomic Rp. 1.071 million by 14 respondents (40%), less than half of the respondents are knowledgeable enough about the positive attitude about the ANC were 21 respondents (60%). Different causes of maternal antenatal care because of parity, socio-economic, maternal knowledge and attitudes about the ANC. Pregnant women with better knowledge, more frequent antenatal visits than pregnant women with less knowledge. The conclusions in this study parity, socioeconomic, knowledge and sikap mother affects mothers in ANC visit. Therefore health workers to provide counseling to pregnant women about the importance of antenatal care through public lectures and interviews with clients, by communicating health messages are organized by the department of health through health centers.